Adherencia al manejo nutricional de adolescentes con malnutrición por exceso: percepción familiar de aciertos y desaciertos - Acuña-Cisterna, Soledad (2018)
Mr. Editor, adolescence facilitates the autonomy and independence of eating behavior, with an increase in the selection and intake of foods with high energy density (1), which favors the presence of excess malnutrition (2), in addition to increase the risk of various cardiometabolic complications (3,4).